The influence of ultrasonic energy on chemical treatment of surface properties and the properties of composites made of luffa cylindrical fiber-polyester resin - KOÇAK, EMİNE DİLARA (ASME-AMER SOC MECHANICAL ENG, 2008)
Producing composites from natural fibers is known to be common. These fibers benefit from their mechanical performances, low density, and their biodegradability. However, it is necessary for the fibers to form adhesion in the matrix. Therefore, it is necessary to apply a chemical process to the surface of the fibers. In this study, four different processes in conventional and ultrasonic energies were applied on luffa cylindrical fibers. At the end of the application, a composite structure was formed on the fibers that were obtained by using unsaturated polyester resin. The changes in the characteristics of the composite structure were recorded by mechanical tests, Fourier transform infrared, X-ray diffractometer, and their morphological characteristics by means of scanning electron microscopy. Considering all the results, formic acid and acetic acid process results were found to adequately modify the fiber surfaces.
Keywords: biofibers; chemical treatment; luffa cylindrical; ultrasonic energy; composites; SORPTION PROPERTIES; MATRIX